(untitled) (International Journal of Food and Nutritional Sciences, 2022)
E-banking has revolutionised the banking industry, offering increased accessibility, convenience and efficiency to users while also enhancing security measures to safe guard sensitive financial information. Venkatesh et al (2012) seven constructs were used. Of 7 UTAUT2 constructs firstly, facilitating condition which is the customer belief that the use of E- banking technology facilitate him / her to do the banking transaction with enjoyment and provides benefit. Secondly, the habit is another strong influencer of the behavioural intention to use online banking facility.